Pemberdayaan Wakaf Tunai Pada Baitul Maal Hidayatullah Di Surabaya Dalam Bidang Pendidikan - Puspita Rachman; Sri Herianingrum (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
The purpose of the research is to knowing the empowerment of cash waqf in the education sector BaitulMaalHidayatullahin Surabaya. So, that case is become the bases of the interview to knowing empowerement of cash waqf to support people welfare through education.The approach of this research is using qualitative approach. Qualitative approach is using case study method. The subject of this research is finance manager and office from Baitul Maal Hidayatullah in Surabaya which will be informant and give various information which during the research.Based on research results has showing the empowerment of cash waqf have a typical impact for education with the build of PesantrenPenghafal Al-Quran Darul Hijrah. Pesantern Darul Hijrah not only teach the students to memorize Al-Qur’an, but also to practice the contents of Al-quran and also supported by various activity in pondok pesantren in accordance with syariah principle which will make a leader to know Al-Qur’an and As-Sunnah very well.